The Implementation of the Peer Tutoring Method to Improve Forward Roll Skills in Floor Gymnastics Learning among Junior High School Students: Implementasi Metode Tutor Sebaya untuk Meningkatkan Keterampilan Roll Depan pada Pembelajaran Senam Lantai Siswa SMP - Muhammad Fahrul; Gunawan Gunawan; Jumain Jumain; Anwar Anwar (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
This classroom action research was conducted to improve students’ learning outcomes in performing the forward roll skill in floor gymnastics through the implementation of peer tutoring. The study involved 36 eighth-grade students of SMP Negeri 6 Palu and was carried out in two cycles following the Kemmis and McTaggart model, which included the stages of planning, action, observation, and reflection. Data were collected using observation sheets and performance tests based on predetermined indicators of motor skill achievement. The results showed that prior to the intervention, only 40% of students achieved the Minimum Mastery Criteria (MMC), with an average score of 70.25. After the implementation of peer tutoring, the percentage of mastery increased to 50% (M = 74.25) in Cycle I, and further improved to 88.9% (M = 82.25) in Cycle II. These findings demonstrate that peer tutoring effectively enhances students’ conceptual understanding, confidence, and motor skill performance in gymnastics. This research contributes to physical education by highlighting the pedagogical novelty of peer tutoring in basic motor skill learning, which has been underexplored in similar contexts.